2017
DOI: 10.5765/jkacap.2017.28.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Addiction Predictably Embedded in Childhood Trauma: A Neurobiological Review

Abstract: The seeds of addiction are typically sown years prior to the onset of addictive substance use or engagement in addictive behaviors, due to the priming of the reward pathway (RewP) by alterations in the mechanism of stress-signaling from the hypothalamic-pituitary-adrenal axis (HPA) and related pathways. Excessive stress from a single-event and/or cumulative life experiences during childhood, such as those documented in the Adverse Childhood Experiences Study, is translated into neurobiological toxicity that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…Past studies have found emotional reactivity/dysregulation and negative affect, such as anxiety and stress, to be correlated with craving and SUD (2,5,29,30). Excessive stress signaling is thought to prime the brain's reward system for addictive behaviors (29). Given the role of the reward system in mediating craving and the known negative effects of adverse childhood experiences on emotional regulation, we suspected ACE scores would be associated with increased reports of craving (31).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Past studies have found emotional reactivity/dysregulation and negative affect, such as anxiety and stress, to be correlated with craving and SUD (2,5,29,30). Excessive stress signaling is thought to prime the brain's reward system for addictive behaviors (29). Given the role of the reward system in mediating craving and the known negative effects of adverse childhood experiences on emotional regulation, we suspected ACE scores would be associated with increased reports of craving (31).…”
Section: Discussionmentioning
confidence: 96%
“…This study is the rst known to evaluate the relationship between ACE score and craving. Past studies have found emotional reactivity/dysregulation and negative affect, such as anxiety and stress, to be correlated with craving and SUD (2,5,29,30). Excessive stress signaling is thought to prime the brain's reward system for addictive behaviors (29).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms found in other genes, such as those in the dopamine reward pathway and those encoding for protein alpha-synclein, are associated with increased craving amongst those with SUD (28-30). These genetic variations are suspected to be speci c to craving and distinct from other genetic pathways underlying the SUD phenotype (29). With that in mind, one study found that there was no difference in alcohol craving between patients in Mexico, Argentina, Poland, and the USA (31).…”
Section: Discussionmentioning
confidence: 99%
“…Seok Hyun Nam, Juhyun Park, and Tae Won Park's study "Clinical aspects of premonitory urges in patients with Tourette's disorder" is a review article that attempted to determine typical symptoms of Tourette's disorder. In JKACAP Vol 28, No 1 published on January 1, 2017, Corwin [2] and scholars from the Academy on Violence and Abuse [3][4][5] published articles concerning childhood trauma and maltreatment. Studies concerning abuse and violence investigate the social phenomenon, rather than specific diseases with definite pathogens or etiologies.…”
mentioning
confidence: 99%